ECTIMA: A CASE REPORT - Julia Arta, I Gde (E-Jurnal Medika Udayana; vol 3 no 3 (2014):e-jurnal medika udayana)
Ektima a superficial ulcer with crusting on it caused by streptococcus B infection hemolyticus. Ektima incidents worldwide are not known precisely. The frequency of occurrence based on age ektima usually found in children and the elderly, there is no distinction of race and gender (male and female alike). In most children at age 6 months to 18 years. Diagnosis of the disease ektima made based on clinical symptoms found in patients and supported by laboratory tests such as Gram's staining. Treatment ektima form of topical and systemic treatment. This report discusses the case Ektima on a boy aged 7 years. These patients receive topical treatment with 0.9% NaCl compress on the wound that is still wet and Mupirocin 2% cream applied thinly 3-4x/day  the lesion and systemic antibiotics such as cefadroxil syrup 2 times daily 1 ½ teaspoons.
Keywords: ektima